Biomechanical performance of cranial implants with different thicknesses and material properties: A finite element study - Marcián, Petr; Narra, Nathaniel; Borák, Libor; Chamrad, Jakub; Wolff, Jan (Computers in biology and medicine, 2019)
This study investigated the effect of implant thickness and material on deformation and stress distribution within different components of cranial implant assemblies. Using the finite element method, two cranial implants, differing in size and shape, and thicknesses (1, 2, 3 and 4 mm, respectively), were simulated under three loading scenarios. The implant assembly model included the detailed geometries of the mini-plates and micro-screws and was simulated using a sub-modeling approach. Statistical assessments based on the Design of Experiment methodology and on multiple regression analysis revealed that peak stresses in the components are influenced primarily by implant thickness, while the effect of implant material is secondary. On the contrary, the implant deflection is influenced predominantly by implant material followed by implant thickness. The highest values of deformation under a 50 N load were observed in the thinnest (1 mm) Polymethyl Methacrylate implant (Small defect: 0.296 mm; Large defect: 0.390 mm). The thinnest Polymethyl Methacrylate and Polyether Ether Ketone implants also generated stresses in the implants that can potentially breach the materials' yield limit. In terms of stress distribution, the change of implant thickness had a more significant impact on the implant performance than the change of Young's modulus of the implant material. The results indicated that the stresses are concentrated in the locations of fixation; therefore, the detailed models of mini-plates and micro-screws implemented in the finite element simulation provided a better insight into the mechanical performance of the implant-skull system.
Keywords: Skull; Computer Simulation; Finite Element Analysis; Cranioplasty; Stress, Mechanical; lebka; počítačová simulace; experimentální implantáty; Humans; lidé; Implants, Experimental; Finite element method; Mechanical properties; 3D printing; Skull implant; analýza metodou konečných prvků; mechanický stres